Transient proteolysis reduction of Nicotiana benthamiana-produced CAP256 broadly neutralizing antibodies using CRISPR/Cas9 - Singh, Advaita Acarya; Pillay, Priyen; Naicker, Previn; Alexandre, Kabamba; Malatji, Kanyane; Mach, Lukas; Steinkellner, Herta; Vorster, Juan; Chikwamba, Rachel; Tsekoa, Tsepo L. (Frontiers in Plant Science, 2022)
The hypersensitive response is elicited by Agrobacterium infiltration of Nicotiana benthamiana, including the induction and accumulation of pathogenesis-related proteins, such as proteases. This includes the induction of the expression of several cysteine proteases from the C1 (papain-like cysteine protease) and C13 (legumain-like cysteine protease) families. This study demonstrates the role of cysteine proteases: NbVPE-1a, NbVPE-1b and NbCysP6 in the proteolytic degradation of Nicotiana benthamiana (glycosylation mutant ΔXTFT)-produced anti-human immunodeficiency virus broadly neutralising antibody, CAP256-VRC26.25. Three putative cysteine protease cleavage sites were identified in the fragment crystallizable region. We further demonstrate the transient coexpression of CAP256-VRC26.25 with CRISPR/Cas9 mediated genome editing vectors targeting the NbVPE-1a, NbVPE-1b and NbCysP6 genes which had resulted in a decrease in CAP256-VRC26.25 degradation. No differences in structural features were observed between the human embryonic kidney 293 (HEK293)-produced and ΔXTFT broadly neutralising antibodies produced with and without the coexpression of genome editing vectors. Furthermore, despite the presence of proteolytically degraded fragments of plant produced CAP256-VRC26.25 without the coexpression of genome editing vectors, no influence on the in vitro functional activity was detected. Collectively, we demonstrate an innovative in planta strategy for improving the quality of the CAP256 antibodies through the transient expression of the CRISPR/Cas9 vectors.